Reporting Errors, Repairing Knowledge: Inside Wikipedia’s Public Knowledge Quality Assurance - Anna Karczewska (European Conference on Knowledge Management, 2026)
This article examines Wikipedia’s user-facing “Report an error” pages as a publicly accessible mechanism of management of knowledge repair and quality assurance. Focusing on selected language versions, the study treats error reports as observable traces of maintenance work: they capture how readers identify errors in articles, how they are articulated, and how the community resolves them. Methodologically, the paper relies on information available on the reporting pages themselves (including the discussions, visible status markers, categories, and archives). The content analysis combines quantitative and qualitative approaches. Resolution outcomes (e.g., fixed, rejected, no action) were measured to approximate the effectiveness of quality work. Qualitatively, the paper analyzed structure of the “Report an error” webpages in different versions, readability of the webpage, the structure of the suggested reports and responses to reports. Comparative analysis across language versions assessed what was the size and composition of the webpage content, and the responsiveness of editors through time-to-first-response and time-to-closure estimated from visible timestamps and status changes. By treating “Report an error” webpages as a tractable lens on knowledge repair, the study contributes an empirically grounded account of how Wikipedia’s quality assurance is enacted in practice, and provides a methodology for evaluating the efficiency of error correcting processes in collaborative knowledge systems.